Comparison of the absolute calibration method with the method of standard addition for the determination of halothane in blood by gas chromatographic headspace analysis - Koupil, P; Novák, J; Drozd, J (Journal of chromatography, 1988)
As long-term exposure to exhaled halothane can be a cause of hepatitis and/or damage to the liver, the determination of halothane in blood is important in clinical practice. Gas chromatographic headspace analysis appears to be the most successful method. In the present study, two methods of quantitative evaluation of the analysis were compared by statistical treatment and direct comparison. The absolute calibration method was found to be unsuitable since it yields entirely unreliable results. This is due to different contents of lipoid and other components in the blood of the normal population, and this influences the vapour phase concentration of halothane and results in different values for the slopes of calibration curves for different blood samples. The standard addition method gives reliable results.
Keywords: chromatografie plynová; Halothane; lidé; Chromatography, Gas; halothan; Triglycerides; Cholesterol; Humans; cholesterol; triglyceridy